Pertumbuhan dan Hasil Tanaman Jagung Manis pada Berbagai Populasi Gulma Chloris barbata (Poaceae) - Kefi, Andreas; Guntoro, Dwi; Santosa, Edi (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2022)
Purpletop chloris (Chloris barbata Sw.) is a dominant weed on maize field in East Nusa Tenggara (ENT), but study on the effect onto maize is rare. The study evaluated the effect of C. barbata on growth and yield of sweet corn. The seed of C. barbata was obtained from farmer field in Kupang Regency, ENT. Experiment was conducted in October 2019 to January 2020 at Cikabayan Experimental IPB Farm, Bogor-Indonesia using a randomized complete block design with five replications. Sweet corn seeds were planted at polybag sized 30 cm x 30 cm filled with 5 kg media with five levels of C. barbata seeds, i.e., 0 (clean weeding), 15, 30, 45, and 60. The results showed that C. barbata suppressed the growth and yield of sweet corn. It suppressed the height and dry weight (DW) at 4 weeks after planting (WAP) where the population of 15 individuals decreased plant height and 30 individuals suppressed the total DW at 8 WAP. A population of 15 individuals reduced stem diameter, leaf area and width, leaf color, and total DW, while the leaf number and its length were significantly reduced by the treatment of 30 individuals per polybag. The weight of the corn with and without husk, and the length of the cobs reduced by the treatment of 45 individuals, i.e., 48.3%, 49.0%, and 77.7% relative to the control, respectively. Inhibition mechanism of C. barbata on sweet corn growth and yield needs further research. Keywords: allelopathy, competition, corn, East Nusa Tenggara, purpletop chloris